Diversity of bladed Bangiales (Rhodophyta) in western Mediterranean: recognition of the genus Themis and descriptions of T. ballesterosii sp. nov., T. iberica sp. nov., and Pyropia parva sp. nov. Issue 5 (15th September 2014) - Sánchez, Noemí; Vergés, Alba; Peteiro, César; Sutherland, Judith E.; Brodie, Juliet; Vis, M.
<x xml:space="preserve">Abstract</x> The diversity of the bladed species of the red algal order Bangiales from the Iberian Mediterranean shores has been reassessed after a detailed study of this region. Prior to this study, 11 bladed species of Bangiales had been reported from Mediterranean waters: Porphyra atropurpurea, P. cordata, P. coriacea, P. dioica, P. linearis, P. purpurea, P. umbilicalis, Pyropia leucosticta, Pyropia koreana (as P. olivii), Py. elongata (as P. rosengurttii) and Py. suborbiculata. A combined analysis of the nuclear nSSU and the plastid rbcL genes together with detailed morphological studies has confirmed the presence of species within the genera Porphyra and Pyropia and also revealed a third, undescribed genus, Themis gen. nov. Porphyra linearis, Pyropia elongata and the introduced Pyropia koreana had been previously listed for the Mediterranean and were recorded in this study. An additional four species, including the introduced Pyropia suborbiculata and three new species: Pyropia parva sp. nov., Themis ballesterosii sp. nov., and Themis iberica sp. nov. were also observed. Hence, most of the Porphyra species traditionally reported along these shores were not reported in this survey. This new floristic Bangiales composition confirms the importance of the Mediterranean basin as a hotspot for biodiversity, possible endemics of ancient origin and high proportion of introductions. Our data also continue to confirm the extent of Bangiales diversity at regional and worldwide levels.